Constraints on the Ecomorphological Convergence of Zooplanktivorous Butterflyfishes. Issue 1 (13th May 2021) - Hodge, J R; Song, Y; Wightman, M A; Milkey, A; Tran, B; Štajner, A; Roberts, A S; Hemingson, C R; Wainwright, P C; Price, S A
Synopsis: Whether distantly related organisms evolve similar strategies to meet the demands of a shared ecological niche depends on their evolutionary history and the nature of form–function relationships. In fishes, the visual identification and consumption of microscopic zooplankters, selective zooplanktivory, is a distinct type of foraging often associated with a suite of morphological specializations. Previous work has identified inconsistencies in the trajectory and magnitude of morphological change following transitions to selective zooplanktivory, alluding to the diversity and importance of ancestral effects. Here we investigate whether transitions to selective zooplanktivory have influenced the morphological evolution of marine butterflyfishes (family Chaetodontidae), a group of small-prey specialists well known for several types of high-precision benthivory. Using Bayesian ancestral state estimation, we inferred the recent evolution of zooplanktivory among benthivorous ancestors that hunted small invertebrates and browsed by picking or scraping coral polyps. Traits related to the capture of prey appear to be functionally versatile, with little morphological distinction between species with benthivorous and planktivorous foraging modes. In contrast, multiple traits related to prey detection or swimming performance are evolving toward novel, zooplanktivore-specific optima. Despite a relatively short evolutionary history, general morphological indistinctiveness, and evidence of constraint on the evolution of body size, convergent evolution has closed a near significant amount of the morphological distance between zooplanktivorous species. Overall, our findings describe the extent to which the functional demands associated with selective zooplanktivory have led to generalizable morphological features among butterflyfishes and highlight the importance of ancestral effects in shaping patterns of morphological convergence.